Will my cat eat my eyeballs? : big questions from tiny mortals about death - Doughty, Caitlin (W. W. Norton & Company, 2019)
"Best-selling author and licensed mortician Caitlin Doughty answers real questions from kids about death, dead bodies, and decomposition. Every day, funeral director Caitlin Doughty receives dozens of questions about death. What would happen to an astronaut's body if it were pushed out of a space shuttle? Do people poop when they die? Can Grandma have a Viking funeral? In the tradition of Randall Munroe's What If?, Doughty's new book, Will My Cat Eat My Eyeballs?, blends her scientific understanding of the body and the intriguing history behind common misconceptions about corpses to offer factual, hilarious, and candid answers to thirty-five urgent questions posed by her youngest fans. Readers will learn what happens if you die on an airplane, the best soil for mummifying your dog, and whether or not you can preserve your friend's skull as a keepsake. Featuring illustrations from Dianne Ruz, Will My Cat Eat My Eyeballs? will delight anyone interested in the fascinating truth about what will happen (to our bodies) after we die"--